Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{x}{5}+\dfrac{1}{2}=\dfrac{6}{10}\\ \dfrac{x}{5}+\dfrac{1}{2}=\dfrac{3}{5}\\ \dfrac{x}{5}=\dfrac{3}{5}-\dfrac{1}{2}\\ \dfrac{x}{5}=\dfrac{6}{10}-\dfrac{5}{10}\\ \dfrac{x}{5}=\dfrac{1}{10}\\ \dfrac{2x}{10}=\dfrac{1}{10}\\ \Rightarrow2x=1\\ x=1:2\\ x=0,5=\dfrac{1}{2}\)
b) \(x+\dfrac{3}{15}=\dfrac{1}{3}\\ x=\dfrac{1}{3}-\dfrac{3}{15}\\ x=\dfrac{5}{15}-\dfrac{3}{15}\\ x=\dfrac{2}{15}\)
c) \(x-\dfrac{12}{4}=\dfrac{1}{2}\\ x-3=\dfrac{1}{2}\\ x=\dfrac{1}{2}+3\\ x=\dfrac{1}{2}+\dfrac{6}{2}\\ x=\dfrac{7}{2}\)
d) \(\dfrac{1}{2}x+\dfrac{1}{2}=\dfrac{5}{2}\\ \dfrac{1}{2}x=\dfrac{5}{2}-\dfrac{1}{2}\\ \dfrac{1}{2}x=2\\ x=2:\dfrac{1}{2}\\ x=4\)
a. \(\dfrac{2x+5}{10}=\dfrac{6}{10}\Leftrightarrow2x=1\Leftrightarrow x=\dfrac{1}{2}\)
b. \(\dfrac{15x+3}{15}=\dfrac{5}{15}\Leftrightarrow15x=2\Leftrightarrow x=\dfrac{2}{15}\)
c. \(\dfrac{4x-12}{4}=\dfrac{2}{4}\Leftrightarrow4x=14\Leftrightarrow x=\dfrac{7}{2}\)
d. \(\dfrac{1+x}{2x}=\dfrac{5x}{2x}\Leftrightarrow-4x=-1\Leftrightarrow x=\dfrac{1}{4}\)
e. \(\dfrac{-4\left(2x-5\right)}{6\left(2x-5\right)}-\dfrac{2}{6\left(2x-5\right)}=\dfrac{9\left(2x-5\right)}{6\left(2x-5\right)}\)
\(\Leftrightarrow-8x+20-2=18x-45\)
\(\Leftrightarrow-26x=-63\Leftrightarrow x=\dfrac{63}{26}\)
a,
Ta có:
\(\frac{11}{12}-\left(\frac{2}{5}+x\right)=\frac{2}{3}\)
\(\Leftrightarrow\frac{55}{60}-\frac{60\left(\frac{2}{5}+x\right)}{60}=\frac{40}{60}\)
\(\Leftrightarrow\frac{55}{60}-\frac{24+60x}{60}=\frac{40}{60}\)
=> 55-24-60x=40
<=> 31-60x=40
<=> x=-3/20
Mấy câu còn lại cũng tương tự thế đó
a; - \(\dfrac{10}{13}\) + \(\dfrac{5}{17}\) - \(\dfrac{3}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{11}{20}\)
= - (\(\dfrac{10}{13}\) + \(\dfrac{3}{13}\)) + (\(\dfrac{5}{17}\) + \(\dfrac{12}{17}\)) - \(\dfrac{11}{20}\)
= - 1 + 1 - \(\dfrac{11}{20}\)
= 0 - \(\dfrac{11}{20}\)
= - \(\dfrac{11}{20}\)
b; \(\dfrac{3}{4}\) + \(\dfrac{-5}{6}\) - \(\dfrac{11}{-12}\)
= \(\dfrac{9}{12}\) - \(\dfrac{10}{12}\) + \(\dfrac{11}{12}\)
= \(\dfrac{10}{12}\)
= \(\dfrac{5}{6}\)
c; [13.\(\dfrac{4}{9}\) + 2.\(\dfrac{1}{9}\)] - 3.\(\dfrac{4}{9}\)
= [\(\dfrac{52}{9}\) + \(\dfrac{2}{9}\)] - \(\dfrac{4}{3}\)
= \(\dfrac{54}{9}\) - \(\dfrac{4}{3}\)
= \(\dfrac{14}{3}\)
Câu 1:
a: \(\dfrac{1}{3}-\dfrac{1}{4}+\dfrac{2}{5}=\dfrac{20-15+24}{60}=\dfrac{29}{60}\)
b: \(\dfrac{1}{3}-\dfrac{4}{5}+\dfrac{4}{3}=\dfrac{5}{3}-\dfrac{4}{5}=\dfrac{25-12}{15}=\dfrac{13}{15}\)
c: \(=\dfrac{1}{2}+\dfrac{1}{6}-\dfrac{1}{4}+\dfrac{1}{5}\)
\(=\dfrac{30}{60}+\dfrac{10}{60}-\dfrac{15}{60}+\dfrac{12}{60}\)
=37/60
a) 3/5 x=4/7+1/5; b)(2x-1/2):3=12;
3/5 x=27/35 (2x-1/2)=12x3
x=27/35:3/5 2x-1/2=36
x=9/7 2x=36+1/2
Vay x=9/7 2x=73/2
x=73/2:2
x=73/4
Vay x=73/4
a: \(\dfrac{1}{6}+x=\dfrac{5}{12}\)
=>\(x=\dfrac{5}{12}-\dfrac{1}{6}=\dfrac{5}{12}-\dfrac{2}{12}=\dfrac{3}{12}=\dfrac{1}{4}\)
b: \(\dfrac{3}{4}+\dfrac{1}{4}x=-\dfrac{1}{2}\)
=>\(\dfrac{1}{4}x=-\dfrac{1}{2}-\dfrac{3}{4}=-\dfrac{5}{4}\)
=>\(x=-\dfrac{5}{4}:\dfrac{1}{4}=-5\)
c: \(x+\dfrac{2}{3}=-\dfrac{1}{12}\)
=>\(x=-\dfrac{1}{12}-\dfrac{2}{3}=-\dfrac{1}{12}-\dfrac{8}{12}=-\dfrac{9}{12}=-\dfrac{3}{4}\)
d: \(\dfrac{1}{5}+\dfrac{4}{5}x=\dfrac{3}{4}\)
=>\(\dfrac{4}{5}x=\dfrac{3}{4}-\dfrac{1}{5}=\dfrac{15}{20}-\dfrac{4}{20}=\dfrac{11}{20}\)
=>\(x=\dfrac{11}{20}:\dfrac{4}{5}=\dfrac{11}{20}\cdot\dfrac{5}{4}=\dfrac{11}{16}\)
🕵🏼♀️🕵🏻🕵🏻♂️🕵🏻👳🏻